2020
DOI: 10.1093/nar/gkaa042
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mRNA translation in neuronal processes and somata by tRNA-FRET

Abstract: In neurons, the specific spatial and temporal localization of protein synthesis is of great importance for function and survival. Here, we visualized tRNA and protein synthesis events in fixed and live mouse primary cortical culture using fluorescently-labeled tRNAs. We were able to characterize the distribution and transport of tRNAs in different neuronal sub-compartments and to study their association with the ribosome. We found that tRNA mobility in neural processes is lower than in somata and corresponds t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 115 publications
1
19
0
Order By: Relevance
“…Local translation may occur at the dendrite level, with proteins transported short distances to activated synapses: this is aligned with the synaptic tagging model, in which synapses share pools of resources, and allocated proteins are somehow "tagged" in order to recruit them to specific synapses (Frey and Morris, 1997;Ainsley et al, 2014;Rogerson et al, 2014). Supporting this theory, ribosome numbers have been found to be elevated in dendritic shafts following LTP induction during the persistent phase of LTP, which is dependent on protein synthesis, and mRNA translation is up-regulated in both the dendrites and soma following LTP induction (Ostroff et al, 2018;Chirillo et al, 2019;Koltun et al, 2020).…”
Section: Protein Synthesis and Plasticitymentioning
confidence: 77%
See 1 more Smart Citation
“…Local translation may occur at the dendrite level, with proteins transported short distances to activated synapses: this is aligned with the synaptic tagging model, in which synapses share pools of resources, and allocated proteins are somehow "tagged" in order to recruit them to specific synapses (Frey and Morris, 1997;Ainsley et al, 2014;Rogerson et al, 2014). Supporting this theory, ribosome numbers have been found to be elevated in dendritic shafts following LTP induction during the persistent phase of LTP, which is dependent on protein synthesis, and mRNA translation is up-regulated in both the dendrites and soma following LTP induction (Ostroff et al, 2018;Chirillo et al, 2019;Koltun et al, 2020).…”
Section: Protein Synthesis and Plasticitymentioning
confidence: 77%
“…Though some studies indicate that dendritic translation is more heavily dependent on free ribosomes than the rough ER ( Koltun et al, 2020 ), it has been found that a healthy ER is necessary for correct dendritic arbor formation ( Cui-Wang et al, 2012 ). Neurons have evolved a unique spatial organization of the secretory system, with satellite ER and Golgi outposts found outside of the soma ( Horton and Ehlers, 2003 ; Aridor et al, 2004 ; Ye et al, 2007 ; Iyer S. C. et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the human genome is composed of ncRNAs that are extensively involved in diverse biological and pathologic activities. tsRNAs are the most common type of small ncRNAs and have been reported to participate in the modulation of RNA processing and protein translation [5,28] . Mounting evidence has shed light on the close association between tsRNAs and various biological processes as well as human diseases, including tumors, diseases of the cardiovascular system, epigenetics, and neurologic disorders [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Koltun et al showed that the level of mRNA translation is similar in neuronal somata and processes and was negatively correlated with the developmental age of living neurons. To show that they used transgenic mice with a reporter gene under the control of the Arc promoter [90], analysis of mRNA trafficking with singlemolecule methods in living neurons confirmed and extended the role of Arc mRNA trafficking in synaptic plasticity and opened new perspectives in neurosciences [91].…”
Section: Arc Mrna Trafficking Within Neuronsmentioning
confidence: 99%